Analysis of Wood Proximate Chemical and Physical Properties of Lubeg (Syzygium lineatum) Tree Species in Apayao, Philippines - Maria Christina Z. Manicad; Hannie T. Martin; Oscar P. Cardenas (Innovations in Biological Science Vol. 9, 2024)
Wood resources continue to play an important role in the world, from packaging materials to buildings and transportation structures. With the worldwide move to intensive forest management to meet wood demand and preserve the environment, the wood supply has been undergoing a significant change in terms of wood quality. Lubeg [Syzygium lineatum (DC.) Merr. & L. M. Perry], a fast-growing lesser-known species could be tapped into the wood utilization industry by exploring their wood proximate chemical and physical properties. The equilibrated ground samples of the wood butt, mid and top portions of the three (3) Lubeg tree species collected in the province of Apayao were analyzed for percent moisture content, percent ash content, percent lignin, percent ethanol cyclohexane, percent holo-cellulose and percent alpha-cellulose content. The data gathered were analyzed using the simple Complete Randomized Design (CRD) and the Least Significant Difference Test (LSD) was used for mean comparison. It was found that the percent moisture content; percent ash content, percent lignin, percent ethanol cyclohexane and percent alpha-cellulose content are highly significant at a 1% level while the percent holo-cellulose content of the Lubeg tree was found to be not significant. These reported findings of the study suggested considerable specific end-uses for Lubeg tree species such as biofuel and as raw material for pulp and paper manufacture. The result of the study showed that the moisture content and relative density of the Lubeg tree at different levels are not significant, and this means that whatever part of the Lubeg tree the moisture content and the relative density are the same. Result of the study revealed that the relative density and percent moisture content of the Lubeg tree falls under the moderately high classification which can be substantially utilized for house and building construction such as posts, beams, trusses, studs, door panels, and flooring, veneer and plywood, bobbins, spindles, bowling pins, bridges, and wharf timber piles and other uses requiring hard and strong wood. On the other hand, volumetric shrinkage of the wood of Lubeg tree falls under moderately low volumetric shrinkage which denotes that the wood can be utilized for high to common-grade furniture manufacture and other uses such as house framing, flooring and ceiling. Also acceptable for millwork/joinery, woodcrafts, novelties, picker sticks and also for musical instruments. It is recommended that studies on the correlations between the chemical and anatomical properties of the Lubeg tree be conducted.